Draft Annual Plan 1988-89 Part I (Introduction and Statements) Government of Mizoram - Planning Commission (Planning Commission, 1988)
Hon'ble Prime Minister of India, Shri Rajiv Gandhi, in his first visit to Mizoram as Prime Minister of India had seen the land, the people and the extent of development works in Mizoram. On seeing the poor infrastructure development and huge backlog of development works, he had detailed a team of Ministers, high officials and experts in various links to visit Mizoram and study the socio-economic problems and also suggest immediate and long term measures to tackle them.
Government of Mizoram, Planning and Programme Implementation Department